Development Assessment of Thinking Skills Interpretation, Analysis, and Inference Prospective Physics Teacher - Marisda, Dewi Hikmah; Handayani, Yusri; Riskawati, Riskawati; Sultan, Ana Dhiqfaini; Hasin, Ardiansah; Nurazmi, Nurazmi; Samsi, Andi Nur (Kasuari: Physics Education Journal (KPEJ), 2022)
This thinks about points to create an appraisal of thinking skills of interpretation, analysis, and inference through analytical essay assessment instruments, worksheets, and problem-solving. Preliminary investigation of the advancement of basic considering aptitudes assessment instruments for prospective Physics teachers in the last 3 (three) years in the Basic Physics course, the test instruments in the Basic Physics course have not been fully oriented to indicators of interpretation, analysis, and inference thinking skills. The process of changing Physics learning, both at the tertiary level and at the secondary school level, is directed at training students to use their thinking potential. One of the Physics learning skills mentioned in Permendikbud Number 64 of 2013 is the development of thinking skills of interpretation, analysis, and inference. This shows that the process and evaluation of learning physics, especially basic physics, should be directed at developing thinking skills in interpretation, analysis, and inference. This inquiry is spurred by the requirement for an appraisal instrument that measures critical thinking skills, especially interpretation, analysis, and inference thinking skills. This study aims to develop an assessment of thinking skills of interpretation, analysis, and inference through analytical essay assessment instruments, worksheets, and problem-solving. This study refers to the 4D Thiagarajan model and produces an assessment that measures the ability to think of interpretation, analysis, and inference. The test instrument was created within the shape of essay analysis, and problem-solving on indicators of thinking skills of interpretation, analysis, and inference. The test instrument was further validated by two experts, and it can be concluded that the created test is exceptionally attainable to utilize.